A simple intervention for stereotypical engagement with an augmentative alternative communicative device. (3rd May 2017) - Cook, Jennifer L.; Rapp, John T.; Burji, Carla; McHugh, Catherine; Nuta, Raluca
Abstract : Although electronic devices may enhance the effectiveness of some behavioral interventions for children with autism spectrum disorders, such devices may also give rise to problem behavior such as repetitious button pressing (i.e., object stereotypy). Results of this study showed that a child with autism spectrum disorder only displayed high levels of object stereotypy on an iPad™ when presses generated auditory output. Subsequently, results showed that when the participant used the iPad™ without auditory output, his stereotypical behavior decreased and his manding for various items simultaneously increased.